Upgrading of Child Educators in Preschool Sexuality Education and Integration of Technologies (Docentes 2.0 Journal, 2022)
Sex education has gained considerable interest in the educational sector, since it constitutes a dimension of the human being expressed throughout life, it goes beyond biological knowledge, explaining processes as important as gender identity, gender role, sex-erotic orientations, and sexual relationships affective in a specific historical-cultural framework, which promotes or limits personality development. This research aimed to identify the sufficiency and effectiveness of the process of overcoming nursery school educators in terms of preschool sex education and integration of Information and Communication Technologies (ICT) in the educational process at CUM Morón (Cuba). The method used was the deductive - inductive, pragmatic paradigm, mixed approach, concurrent type, and concurrent triangulation design. The study sample was intentional, with 40 participants, students with bachelor’s degrees in Preschool Education, linked to children's circles. The instruments used were interviews, surveys, observation, and analysis of documents as data collection tools. The investigation allowed us to conclude with the need to make modifications to the bachelor’s degree in Preschool Education program, incorporating optional subjects, short courses on preschool sexuality, and the use of ICT as tools for the teaching process.
Keywords: Preschool sexuality; ICT; early childhood educators; self-improvement